Recent trend in mixed-model assembly line balancing optimization using soft computing approaches - Razali, Muhamad Magffierah; Kamarudin, N.H.; M. F. F., Ab Rashid; Ahmad Nasser, Mohd Rose (Emerald Group Publishing Ltd., 2019)
Purpose - This paper aims to review and discuss four aspects of mixed-model assembly line balancing (MMALB) problem mainly on the optimization angle. MMALB is a non-deterministic polynomial-time hard problem which requires an effective algorithm for solution. This problem has attracted a number of research fields: manufacturing, mathematics and computer science.